Un système alimentaire métropolitain à São Paulo - Angèle Proust (EchoGéo)
This article examines the place of wholesale markets in the food system of São Paulo and assesses their potential in terms of urban governance for the metropolis. Wholesale markets polarize food produced on a continental scale and ensure a constant supply to the margins. However, the highly centralized nature of food distribution also demonstrates the fragility of a deterritorialised production system that tends to encourage distant areas to the detriment of the metropolitan market garden belt. We will use this example to question the resilience and sustainability of the food system in São Paulo and discuss the implementation of urban food governance.